(3MGTjI Ydi TQM GdJLQjOs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3aEf bhdg ge ehUhahf HRjGOI GdcQe Ydi ef YOGge ef (B.. (3jMJed Gf jchf eYfGg Cf cd hGMO efge ehUha HRjGOI GdcQe Ydi eG YOGg Ch Ydis
(3BNQgG (B:s
(3BNQgG(B: (3hjecf GdLhGH HCf GdeaQhV Cf GdMQcI (B.. (3eSJMjdI aj GdhGbY ceG gh GdTb GdKGfj aYQV EecGfgG Ydi (B... (3GdhGbY jSJMjd Cf jchf eecf Ydi JbOjQ CeQ eecf aj GdhGbY hEdG dRe chfs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds